2018
DOI: 10.1111/ajt.14491
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic ex vivo kidney perfusion for graft quality assessment prior to transplantation

Abstract: Normothermic ex vivo kidney perfusion (NEVKP) represents a novel approach for graft preservation and functional improvement in kidney transplantation. We investigated whether NEVKP also allows graft quality assessment before transplantation. Kidneys from 30-kg pigs were recovered in a model of heart-beating donation (group A) after 30 minutes (group B) or 60 minutes (group C) (n = 5/group) of warm ischemia. After 8 hours of NEVKP, contralateral kidneys were resected, grafts were autotransplanted, and the pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…The same group showed that kidney assessment during warm perfusion might lead to transplantation of initially discarded DCD kidneys [49]. Extending normothermic perfusion to longer periods (2 to 8 hours) has been explored in pig studies [50][51][52][53][54]. Kidneys not suitable for transplantation have been normothermically perfused for 24 hours, making use of urine recirculation, though not transplanted [55].…”
Section: Normothermic Kidney Perfusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group showed that kidney assessment during warm perfusion might lead to transplantation of initially discarded DCD kidneys [49]. Extending normothermic perfusion to longer periods (2 to 8 hours) has been explored in pig studies [50][51][52][53][54]. Kidneys not suitable for transplantation have been normothermically perfused for 24 hours, making use of urine recirculation, though not transplanted [55].…”
Section: Normothermic Kidney Perfusionmentioning
confidence: 99%
“…The kidney quality score is detailed below ( Table 1). Biomarkers determined in the perfusate of pig kidneys undergoing 8 hours of normothermic perfusion after exposure to 0, 30, or 60 minutes of warm ischemia showed that markers of acid-base homeostasis (pH, HCO3-, base excess) correlated with posttransplant renal function [50]. Similarly, lactate and AST were lowest in non-injured grafts and levels correlated with posttransplantat kidney function [50].…”
Section: Normothermic Perfusate Injury Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine perfusion has been developed as an alternative preservation method to cold storage (CS) with promising results in organ quality improvement . Different perfusion protocols have been studied by many groups and among the emerged perfusion protocols, normothermic machine perfusion has gained more attention as it provides the feasibility of assessing organ viability and function before transplant . It has also been shown that gradual rewarming from hypothermic to normothermic is superior to sudden normothermic perfusion after CS .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Different perfusion protocols have been studied by many groups and among the emerged perfusion protocols, normothermic machine perfusion has gained more attention as it provides the feasibility of assessing organ viability and function before transplant. 6,7 It has also been shown that gradual rewarming from hypothermic to normothermic is superior to sudden normothermic perfusion after CS. 4,8 Although gradual rewarming solves the problem strategically, it remains to be established whether there is a need for oxygen carrier during gradual rewarming for providing a sufficient amount of oxygen.…”
Section: Introductionmentioning
confidence: 99%